The role of tourism in environmental protection in Kalar district - رشید, ا.د. شيروان عمر رشيد; محمد, م.م. أزهين كريم محمد (Sulaimani Journal for Humanities, 2025)
The aim of this research is to examine the role of tourism in environmental conservation and mitigating ecological issues in the Kalar District, by identifying the environmental challenges facing the district, which have emerged as a result of climate change and human activities. Additionally, the study proposes necessary solutions by leveraging the region's tourism potential. To achieve the research objectives, data was initially collected from official sources and organizations, followed by the presentation of findings in various tables. Furthermore, spatial data on environmental phenomena were obtained using Google Earth Pro and reorganized and displayed in map form using Geographic Information Systems (GIS). Under the framework of its objectives, the study is divided into three main themes. The first theme establishes the theoretical foundation, discussing the concept of the environment and the role of tourism in environmental preservation. The second theme focuses on the tourism potential of the Kalar District. The third theme addresses the environmental issues in the district and explores strategies for addressing them. Finally, the research concludes with a set of key findings and recommendations.
Keywords: Environment; Tourism; Kalar District; Environmental Issues development